RADIONUCLIDES AND OTHER ELEMENTS DISTRIBUTION IN THE CATALÃO I PHOSPHATE ORE ROCKS, BRAZIL, AND THEIR INDUSTRIAL (BY) PRODUCTS - Conceição, F. T.; Bonotto, D. M.; Jimenez-Rueda, J. R.; Oliveira, E. G.; Mancini, L. H.; Duarte, C. R.; Navarro, R. B. (Geochimica Brasiliensis, 2012)